THE EFFECT OF PHYSICS LEARNING USING FUTURE SELF DIGITAL AVATARS ON STUDENTS' MOTIVATION AND LEARNING RESILIENCE - Laelatul Munawaraha; Muhammad Aminuddin (Jurnal Inovasi Fisika dan Edukasi, 2025)
Physics learning using future self digital avatars constitutes an important aspect of physics education because traditional instructional approaches often fail to sustain students’ motivation and resilience in facing challenging concepts and problem-solving tasks. This limitation highlights the need for further research focusing on innovative digital strategies that leverage self-representative avatars to enhance learning engagement and perseverance. This study aims to examine the effect of physics learning mediated by future self digital avatars on students’ motivation and learning resilience. The research employed a quantitative approach with an experimental method and a quasi-experimental design involving an experimental group and a control group. Data were collected using standardized motivation questionnaires, learning resilience scales, and instructional documentation. The collected data were analyzed using descriptive statistics and inferential analysis through independent samples t-tests. The results indicate that students who participated in physics learning using future self digital avatars demonstrated significantly higher motivation scores (M = 82.4; SD = 5.9) and learning resilience (M = 79.6; SD = 6.3) compared to the control group (motivation: M = 70.2; SD = 7.1; resilience: M = 68.5; SD = 7.8), with statistically significant differences (motivation: t(58) = 6.12, p < 0.001; resilience: t(58) = 5.87, p < 0.001) and strong effect sizes (Cohen’s d = 0.90 and 0.88, respectively). These findings suggest that integrating future self digital avatars into physics learning effectively strengthens students’ intrinsic motivation and their capacity to persist through challenging learning tasks. The study provides significant contributions to the advancement of physics education at both national and international levels by offering an innovative pedagogical model that combines digital self-representation, motivational scaffolding, and resilience-building strategies. Furthermore, the findings are expected to serve as a reference for future research on digital avatar–mediated learning, student motivation, and resilience in science education, as well as to encourage further development of immersive and personalized instructional approaches.